MOTIVATION OF FRESH GRADUATE STUDENTS WHO LEAVE A FAMILY BUSINESS - Evaldo Hans S.R; Mirza Dwi Ilmawan; Aditya Narendra Wardhana (Jurnal Manajerial, 2019)
The purpose of this study is to examine some of the main reasons for successor from family businesses who do not want to continue their family business. This study uses qualitative methods using the approach of in-depth interviews with respondents. The research respondents were fresh graduates who did not want to continue the family business that had been initiated by a large family of respondents. The findings in this study prove that respondents prefer to avoid conflicts with relatives or the absence of succession in family business. Career opportunities from other companies are another factor in making decisions to leave the family business.